2022
DOI: 10.3389/fnins.2022.897225
|View full text |Cite
|
Sign up to set email alerts
|

No Effects of Photobiomodulation on Prefrontal Cortex and Hippocampal Cytochrome C Oxidase Activity and Expression of c-Fos Protein of Young Male and Female Rats

Abstract: The role of light in our biological processes and systems is extensively known. In addition, the use of light devices has been introduced in the field of healthcare as an opportunity to administer power light at specific wavelengths to improve our body functions and counteract light deficiency. One of these techniques is photobiomodulation (PBM), which uses red to infrared light in a non-invasive way to stimulate, heal, regenerate, and protect tissue. The main proposed mechanism of action is the stimulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Our previous study demonstrated that PBM has no effect on normal animals 68 . Moreover, a recent study measured the impact of PBM (810 nm laser, continuous wave, from postnatal day 24 to day 28) on the hippocampus of healthy rat pups, and no significant metabolic alternations were observed 78 . To explore if early PBM treatment can influence postnatal development and behavioral outcomes in normal animals, we also examined weight change of animals treated with PBM alone.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study demonstrated that PBM has no effect on normal animals 68 . Moreover, a recent study measured the impact of PBM (810 nm laser, continuous wave, from postnatal day 24 to day 28) on the hippocampus of healthy rat pups, and no significant metabolic alternations were observed 78 . To explore if early PBM treatment can influence postnatal development and behavioral outcomes in normal animals, we also examined weight change of animals treated with PBM alone.…”
Section: Resultsmentioning
confidence: 99%
“…It is essential to analyse the effect of PBM including sex as an independent variable, to avoid sex and gender bias in neuroscience research [ 26 , 30 ]. To address this issue, analyses were performed considering treatment and sex as the main factors and also the interaction effect between them, aligned with previous studies [ 28 ]. No Sex x Treatment interaction effect was found in any brain region, but analyses revealed sex differences, showing that CCO activity in CG, CA1, CA3, RSG, RSD, and PAR is higher in males.…”
Section: Discussionmentioning
confidence: 99%
“…In this line, the study of Mällo et al (2009) revealed sexual dimorphism, with males displaying a higher CCO activity under control and stress conditions [ 31 ], similar to [ 32 ]. Also, CCO expression has been found to differ between sexes in several behavioural tasks [ 28 , 33 35 ], emphasising the need to include females in experimental and preclinical studies to determine whether they respond differently.…”
Section: Discussionmentioning
confidence: 99%
“…This result corresponds to publication showing no metabolic change by PBM in healthy animal brain. The authors of this manuscript claim that PBM therapy would be effective in subjects whose normal physiology is compromised [78]. In addition, no response of PBM in other brain areas where minimal damage from PI induced SE is expected (Additional file 1: Fig.…”
Section: Discussionmentioning
confidence: 99%